Salivary levels of five microorganisms of root caries in nursing home elderly: a preliminary investigation - Lin Chen; Yuandong Qin; Yuhong Lin; Minquan Du; Yuhong Li; Mingwen Fan (BMC, 2023)
Abstract Background Streptococcus, Bifidobacteria, Lactobacillus and Actinomyces are acidogenic aciduria that may be associated with root caries (RC). The aim of the study was to analyze Streptococcus mutans (S. mutans), Streptococcus sobrinus (S. sobrinus), Bifidobacterium spp., Lactobacillus spp. and Actinomyces naeslundii (A. naeslundii) in the saliva of nursing home elderly, to assess the correlation between bacterial composition and RC for five putative catiogenic organisms. Methods In this study, we collected 43 saliva samples and divided into two groups: the root caries group (RCG, n = 21) and the caries-free group (CFG, n = 22). Bacterial DNA was extracted from the saliva samples. The presence and abundance of the five microorganisms were detected by Quantitative real-time PCR (qPCR). Spearman correlation test was performed to evaluate the relationship between the numbers of root decayed filled surfaces (RDFS) and root caries index (RCI) and salivary levels of the bacteria. Results The salivary levels of S. mutans, S. sobrinus, Bifidobacterium spp. and Lactobacillus spp. were significantly higher in RCG than in CFG (p < 0.05). RDFS and RCI (RDFS/RCI) were positively associated with salivary levels of S. mutans, S. sobrinus and Bifidobacterium spp. (r = 0.658/0.635, r = 0.465/0.420 and r = 0.407/0.406, respectively). No significant differences in presence and amounts of A. naeslundii was observed between the two groups (p > 0.05). Conclusion S. mutans, S. sobrinus and Bifidobacterium spp. in saliva appear to be associated with RC in the elderly. Taken together, the findings indicate that specific salivary bacteria may be involved in the progression of RC.